Implementasi Proyek Penguatan Profil Pelajar Pancasila (P5) Melalui Program Syarat Kecakapan Ubudiyah (SKU) di SMPI Almaarif 01 Singosari Malang: Implementation of Project to Strengthen Pancasila Student Profile (P5) Through Syarat Kecakapan Ubudiyah (SKU) Program at SMPI Almaarif 01 Singosari Malang - Maulana Fatih Falahuddin; Salamah, Umi; Siti Mutholingah (STAI Ma'had Aly Al-Hikam Malang, 2024)
Technology is one of the main triggers for the dynamics of life in various sectors, including the education sector, such as curriculum development. Currently, Indonesia is implementing the Independent Curriculum (Kurikulum Merdeka). The aim is to produce graduates who have a Pancasila Student Profile (Profil Pelajar Pancasila) with six indicators: 1) Faith and devotion to Almighty God and noble character, 2) Global diversity, 3) Working together, 4) Independence, 5) Thinking critically, and 6) Thinking creative. These six indicators were internalized at Islamic Junior High School (SMPI) Almaarif 01 Singosari, Malang Regency, in the Project for Strengthening Pancasila Student Profiles (Projek Penguatan Profil Pelajar Pancasila P5) through the Ubudiyah Skill Requirements (Syarat Kecakapan Ubudiyah; SKU) program. This research aims to answer the problem statement: 1) How is P5 implemented through SKU at SMPI Almaarif 01 Singosari? 2) What are the results of implementing P5 through SKU at SMPI Almaarif 01 Singosari. This article uses a qualitative approach and case study research type. Data was obtained through observation, interviews and documentation techniques. Then analyzed using the Miles, Huberman & Saldana interactive model which includes data condensation, data display and conclusion. The research findings are that the implementation of P5 through the SKU Program at SMPI Almaarif 01 Singosari consists of planning, implementation and results. Planning phase refers to the SKU Guidebook. Implementation is based on the six dimensions of the Pancasila Student Profile. The result is improvement of students’ cognitive, affective and psychomotor qualities. Teknologi menjadi salah satu pemicu utama dinamika kehidupan di berbagai sektor, termasuk sektor pendidikan, seperti pengembangan kurikulum. Saat ini, Indonesia menerapkan Kurikulum Merdeka. Tujuannya untuk membentuk lulusan yang memiliki Profil Pelajar Pancasila dengan enam indikator: 1) Beriman dan bertakwa kepada Tuhan Yang Mahaesa serta berakhlak mulia, 2) Berkebinekaan global, 3) Bergotong-royong, 4) Mandiri, 5) Berpikir kritis, dan 6) Berpikir kreatif. Di Sekolah Menengah Pertama Islam (SMPI) Almaarif 01 Singosari, Kabupaten Malang, keenam indikator tersebut diinternalisasikan dalam Projek Penguatan Profil Pelajar Pancasila (P5) melalui program Syarat Kecakapan Ubudiyah (SKU). Artikel ini menggunakan pendekatan kualitatif dan jenis penelitian studi kasus. Data diperoleh melalui teknik observasi, wawancara dan dokumentasi. Lalu dianalisis dengan model interaktif Miles, Huberman & Saldana yang meliputi kondensasi data, penyajian data dan penarikan kesimpulan. Temuan penelitian adalah implementasi P5 melalui Program SKU di SMPI Almaarif 01 Singosari terdiri dari perencanaan, implementasi dan hasil implementasi. Perencanaan mengacu pada Buku Pedoman SKU. Implementasi didasarkan pada enam dimensi Profil Pelajar Pancasila. Hasil implementasi meliputi peningkatan kualitas kognitif, afektif dan psikomotorik siswa. Kata Kunci: Kurikulum Merdeka; P5; Syarat Kecakapan Ubudiyah (SKU); Profil Pelajar Pancasila; SMPI Almaarif Singosari.